Estimation of some antioxidants for people exposed to electromagnetic waves for Internet towers in Samarra - Methaq Nazhan Mahmood; Asmaa Hashim Shaker; Humam E. Mohammed (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The current study was conducted in Samarra city, as a preliminary study to explore the impact of the presence of Internet network towers inside cities and on residential homes and its impact on people exposed directly and indirectly. The study included collecting samples from people exposed to the radioactive frequencies of Internet towers for periods ranging from (1-5) years and from (5- 10) years. The number of samples was 43 samples of females and males exposed (present in the places where the constellations are located), and 20 samples not exposed (in places far from the towers) as a control group, and the ages ranged between (20-35) years. Analysis and measurements were made for some antioxidants because it is one of the most essential lines of defense against free radicals that cause many diseases and premature aging, which included the concentration of the enzyme glutathione peroxidase PGx, the enzyme superoxide dismutase SOD, glutathione GSH, dimalondhyde MDA, and ONOO. The results showed a significant increase in the level of glutathione peroxidase enzyme concentration and the concentration of superoxide dismutase in the blood serum for people exposed to electromagnetic waves from the Internet towers compared to the control group. The results also showed a significant decrease in the level of GSH in the blood serums of people exposed to electromagnetic waves of the Internet towers compared to the control group. The results also showed a significant increase in the concentration of both MDA and peroxynitrite ONOO compared to the non-exposed subjects in the control group.